2021
DOI: 10.3390/f12060718
|View full text |Cite
|
Sign up to set email alerts
|

Operational Parameters of Logging Trucks Working in Mountainous Terrains of the Western Carpathians

Abstract: Timber haulage is the last phase of the raw timber production process, necessary to transport timber to the customer. To improve the efficiency of logging truck operations, it is necessary to observe and assess several operational parameters through the electronic systems installed on the logging trucks. Measurements for this study were conducted for three logging truck types, which hauled 24,648 m3 of timber over 54,857 km and 1232 round trips. The RMC system was used for truck monitoring, equipped with a CAP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…A multiple regression analyzed the effect of 49 1972.858X (Table 6). An increase in the hauled timber Similar research also indicated a relatively strong negative correlation between hauling productivity and distance, ranging from r = 0.47 to r = 0.68 (Allman et al 2021).…”
Section: Hauling Performancementioning
confidence: 66%
“…A multiple regression analyzed the effect of 49 1972.858X (Table 6). An increase in the hauled timber Similar research also indicated a relatively strong negative correlation between hauling productivity and distance, ranging from r = 0.47 to r = 0.68 (Allman et al 2021).…”
Section: Hauling Performancementioning
confidence: 66%
“…When considering transporting timber from a roadside landing to various destinations, we usually choose a logging truck or a truck with a trailer (Fig. 1) based on its size and load capacity, the commodity being transported, and the technical parameters of the roads used (Allman et al 2021). A qualified (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The purpose of transporting wood is that it can continuously arrive at its destination at the right time with minimal cost. This is appropriate Allman et al (2021); British Columbia Forest Safety Council (2015); Koirala et al (2017) transportation of timber from the forest to the processing facilities is a major component of forest operations. Logging trucks play a critical transportation role in moving logs.…”
Section: Introductionmentioning
confidence: 99%